Cross-sectional patient survey of biological medicine users in Finland to investigate the types of guidance needed by patients in order to carry out their treatment successfully - Tuire Prami; Mari Pölkki (BMJ Open)
Background The use of new biological medicines as standard treatment is expected to increase substantially and cover new therapeutic indications in the near future. Interchange of biological medicines in pharmacies increases the need for patient guidance.Objectives The study aims to gain a patient perspective on biological medicine users’ needs and wishes regarding patient guidance by exploring what kind of information patients wish to receive and to further investigate the potential differences in needs between originator biological medicine users and biosimilar users.Design A cross-sectional patient survey.Setting Anonymous electronic patient survey was conducted in 88 community pharmacies and via two patient organisations in Finland in 2022.Participants Users of originators and biosimilars of adalimumab, etanercept, filgrastim and pegfilgrastim.Results The majority of the 199 respondents had received instructions from a nurse or a public health nurse on how to use their self-injected medicine. According to the patients, the main factors affecting treatment persistence, apart from treatment effectiveness, were few adverse effects, access to treatment support and an easy-to-use administration device. At treatment initiation, the optimal types of guidance were face-to-face instruction, hands-on practice with injecting the medicine, using the administration device and information on adverse effects. Even though 79% of respondents indicated that they would not have wanted more instruction on using their self-injected medicine, these respondents also expressed that, at the time of treatment initiation, additional information or help would have been needed concerning adverse effects, biosimilars, and biological medicines in general. In general, biosimilar users were more concerned about adverse effects than users of originator products.Conclusion Patients consider information about adverse effects an important part of patient guidance when starting and maintaining self-administered biological therapy. The results highlight the importance of ensuring that up-to-date evidence-based information is readily available to patients from reliable sources.